2017
DOI: 10.1186/s10194-016-0712-z
|View full text |Cite
|
Sign up to set email alerts
|

Excitability of the motor cortex in patients with migraine changes with the time elapsed from the last attack

Abstract: BackgroundMotor-evoked potentials (MEPs) produced by single-pulse transcranial magnetic stimulation (TMS) of the motor cortex can be an objective measure of cortical excitability. Previously, MEP thresholds were found to be normal, increased, or even reduced in patients with migraine. In the present study, we determined whether the level of cortical excitability changes with the time interval from the last migraine attack, thereby accounting for the inconsistencies in previous reports.MethodsTwenty-six patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 37 publications
4
27
0
Order By: Relevance
“…There are very inconsistent results about these parameters in current literature in migraine patients. Decreased or similar intracortical inhibition found in interictal migraineurs compared to controls. ICF is considered as a sum of the NMDA glutamatergic facilitation and GABA‐related inhibition .…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…There are very inconsistent results about these parameters in current literature in migraine patients. Decreased or similar intracortical inhibition found in interictal migraineurs compared to controls. ICF is considered as a sum of the NMDA glutamatergic facilitation and GABA‐related inhibition .…”
Section: Introductionmentioning
confidence: 78%
“…4 Resting motor threshold (RMT), cortical silent period (CSP), short-interval intracortical inhibition (SICI), long-interval intracortical inhibition (LICI), and intracortical facilitation (ICF) are parameters that represent different intracortical motor inhibitory and facilitatory mechanisms. [5][6][7] Studies about RMT found no significant difference between interictal migraineurs and healthy controls, [8][9][10] but RMT seems to be related to the time elapsed between migraine attack and measurement. 9 CSP, SICI, and LICI are related to motor cortical GABAergic inhibition mechanisms.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…There is increasing evidence that adult migraine results from an imbalance of excitation/inhibition in the brain, which changes cyclically until a migraine occurs (known as the migraine cycle). 8,9 During the interictal period, excitability of the cortex increases proportionally with time to the next attack. During the migraine or shortly thereafter, the brain returns back to baseline activity and begins the cycle again.…”
Section: Introductionmentioning
confidence: 99%
“…During the migraine or shortly thereafter, the brain returns back to baseline activity and begins the cycle again. 8,9 Neurophysiological studies suggest this cortical hyperexcitability is a result of abnormal thalamic control. 10 Studies have revealed that, in migraine, there is altered communication in the thalamo-cortical networks11 which underlie important processes in multisensory integration; this altered communication is associated with clinical migraine symptoms.…”
Section: Introductionmentioning
confidence: 99%